2018
DOI: 10.4314/ajcem.v19i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of microbial, proximate and heavy metal compositions of some gastropods, bivalve and crustacean seafood

Abstract: Background: Seafood are known to be nutritionally rich, however, water bodies from where these foods are harvested are often burdened with wastes from industries, household and run-offs. Thus seafood can harbor pathogenic microorganisms and heavy metals which can pose a serious health hazard to consumers. Materials and Methods: In this study, 5kg each of Littorina littorea, Achatina fulica,Tympanotonos fuscatus, Dorsanum miran, Egeria radiate and Penaeus notialis were investigated for microbial, proximate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Copper and cadmium were higher during the wet season at both locations. Similar results for heavy metal composition were reported by Capeme et al [19] and Oranusi et al [20]. The results were significant for the Pearson correlation coefficient at p(0.05) r (cal) 0.814<r (tab) 0.947.…”
Section: Resultssupporting
confidence: 89%
“…Copper and cadmium were higher during the wet season at both locations. Similar results for heavy metal composition were reported by Capeme et al [19] and Oranusi et al [20]. The results were significant for the Pearson correlation coefficient at p(0.05) r (cal) 0.814<r (tab) 0.947.…”
Section: Resultssupporting
confidence: 89%
“…The G. paradoxa is a good source of protein, however, it has a great tendency to harbour pathogenic microorganisms, especially those that are harmful to human health due to the unsanitary conditions of the water bodies where aquatic animals are cultivated [23]. The isolation of bacterial isolates from G. paradoxa is a good source of protein, however, it has a great tendency to harbour pathogenic microorganisms, especially those that are harmful to human health due to the unsanitary conditions of the water bodies where aquatic animals are cultivated [23] The high incidence of S. aureus and E. coli in our study corroborates the studies carried out by Ekanem and Adegoke [6]; Oranusi et al [24] and Ekanem [25], who observed high levels of pathogens in aquatic organisms. However, our results differ from those obtained by Udoh et al [26] who obtained fewer pathogenic bacteria in G. paradoxa samples from Cross River, Nigeria.…”
Section: Discussionsupporting
confidence: 88%
“…Thereafter, the discrete colonies were sub-cultured onto plates of freshly prepared nutrient agar and aerobically incubated at 37°C for 24 hr. The pure cultures of isolates were streaked onto nutrient agar slants, incubated at 37°C for 24…”
Section: Bacteriological Analyses Of Samplesmentioning
confidence: 99%
“…In order to protect human health, appropriate control measures to eliminate human pathogen should be developed. Oranusi et al [30] found the microbial loads of the seafood's were more than acceptable standard (significantly higher in gastropods, p≤0.05). Water body protection and seafood monitoring were necessary.…”
Section: Good Treatement Of Household Equipment and Foodsmentioning
confidence: 96%